Pengaruh Digitalisasi dan Kompetensi Sumber Daya Manusia terhadap Pertumbuhan Usaha Kecil dan Menengah (UKM) - Nurhasanah; Rully Lesmana; Pitri Yana Ariyanti; Hikmah Ayu Sira; Ade Farma Pusfita Sari; Nadia Rahma Dhani; Sri Agus Tina (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study found that digitalization has a positive and significant effect on the growth of SMEs in Indonesia. Technology-based administrative systems, product distribution through e-commerce platforms, and the use of social media for promotion can help SMEs perform better. Thus, SMEs can expand their customer network, increase revenue, and improve operational efficiency. Therefore, SMEs need support from various parties, including the government and the private sector, to transform themselves into digital businesses. This must be done through training, digital infrastructure, and supportive policies to maintain competitiveness in the digital economy era.